Network Traffic Monitoring with IDS (International Journal of Advanced Research in Computer Science, 2017)
Security is a big issue for all networks in todayâ€™s enterprise environment. Many methods have been developed to secure the networkinfrastructure and communication over the Internet, among them the use of firewalls, encryption, and virtual private networks. Intrusion detection is arelatively new addition to such techniques. IDSes protect a system from attack, misuse, and compromise. It can also monitor networkactivity.Network traffic monitoring and measurement is increasingly regarded as an essential function for understanding and improving theperformance and security of our cyber infrastructureÂ Keywords: IDS, NTM, Pattern Matching, IMAP